ASYLUM LAW REGULATION AND CURRENT EVENTS OF ITS APPLICATION IN LATVIA - Gaveika, Arturs; Bulgakova, Ilona (Border Security and Management, 2016)
The development of the regulatory framework of Latvia’s Asylum and external border is determined by international regulatory framework, the EU's regulatory framework and influence of Latvian bilateral relationship as well as the need to balance the free movement of persons which is essential part of human rights in order to ensure the legislation in relation to Latvian external border regime within international and national legal framework. This is evidenced as a problematic issue in regulatory framework, law practices and border control both in Latvia and other EU countries. It is necessary to explore international, EU and national legal framework within the EU's external borders functioning in Latvia by detecting problems in the EU's Asylum determination in the context of border regime and border control regulatory framework, by exploring legislation, legal concepts, incompleteness of terminology and eventually to develop suggestions for improving laws and regulations. The primary method is Analytical method - the analysis of international, EU, the Schengen Acquis and the national regulatory framework and administrative practice.